The Research Evolution and Frontier Analysis of Historical Districts in Ancient Villages by Space Syntax - Junzhang Chen (PT FORMOSA CENDEKIA GLOBAL, 2022)
The article uses CNKI and Google Scholar as the main document search methods. Through induction and analysis, it can be found that the call for urban renewal in Zhuhai has been sounded at this stage. The ancient villages in different areas of the city, such as Tangjiahuitong Village, Doumen Nanmen Village, and Nanping Beishan Village, have been given a certain degree by related scholars. For in-depth research, many journals and master and doctoral papers already have relevant documents available for retrieval. Through the analysis of relevant literature, we can see that the research method is a combination of quantitative and qualitative analysis, and some new results have been obtained through the analysis. In recent years, Qianshan Cuiwei Village also has some related literature studies, but there are few literatures. The literature is mainly It is a qualitative analysis and research, and there is no quantitative analysis. In the future, relevant scholars can start with quantitative analysis, and space syntax may be a good method. In the feasibility study of Cuiwei Village using this method, it was found that the spatial syntax has certain limitations at the geographic scale. Therefore, how to apply the spatial syntax scientifically, rationally and effectively in the village research is a question worthy of discussion in the future.